Edukasi Pengelolaan Sampah Dengan Teknologi Daur Ulang Dalam Rangka Mewujudkan Kemandirian Yayasan Pondok Pesantren Darul Khuldi - Safril Kartika Wardhana; Maulidia Berlianti; Ahmad Zikri; Anjar Siti Mashitoh; R Zicky Chandra Kesuma (Universitas Dehasen Bengkulu, 2024)
Waste management in Kabupaten Ogan Komering Ulu is still facing problems. The size of the waste pile is not commensurate with the waste handling capacity. Plastic waste is a source of problems in landfills because it is quite large and difficult to decompose. Through research and innovation in waste management, we hope to create solutions that not only minimize negative impacts on the environment, but also create new opportunities for a sustainable economy. This research will be carried out at the Darul Khuldi Islamic Boarding School Foundation in Ogan Komering Ulu Regency. This research was conducted to process waste at the Darul Khuldi Islamic Boarding School Foundation, namely domestic waste in the form of plastic waste and organic waste. Plastic waste produced during activities carried out at the Islamic Boarding School is processed into pelleting plastic pellets and making ecoenzymes to manage organic waste. The results obtained are expected to increase the independence of the Darul Khuldi Islamic Boarding School Foundation and reduce the impact of pollution on the surrounding environment